Experimental study of heat transfer by water flowing through smooth and rough rock fractures - Yinfei Luo; Weilin Xu; Yude Lei; Ping Wu; Guangxiong Qin; Ruishou Ba (Energy Reports, 2019)
It is important to have an accurate understanding of heat transfer process of water flowing through fractures for geothermal energy extraction and utilization. We designed an experiment to study the convective heat transfer characteristics of distilled water pumped through manmade smooth and rough fractures in granite samples. The flow velocity, permeating pressure, confining pressure, inlet and outlet fluid temperature and rock outer-surface temperature were measured and recorded to calculate the heat transfer coefficient. The effects of volumetric flow rate, fracture surface roughness, and outer wall surface temperature on the convective heat transfer process were analyzed. The results indicate that fracture surface roughness has a great influence on the heat transfer characteristics of water flowing through rocks. Overall heat transfer intensity improved along with an increase in rock fracture surface roughness. Our results have implications for geothermal energy extraction and utilization.
Keywords: 330; Enhanced geothermal system; Heat transfer; Rock fracture